Diagnostic accuracy of 3D magnetic resonance elastography for assessing histologic grade of hepatocellular carcinoma: comparison of three methods for positioning region of interest. - Liu, Weimin; Rong, Dailin; Zhu, Jie; Xiao, Yuanqiang; Zhang, Linqi; Deng, Ying; Chen, Jun; Yin, Meng; Venkatesh, Sudhakar K.; Ehman, Richard L.; Wang, Jin (Abdominal Radiology, 2021)
Purpose: To assess the influence of region of interest (ROI) placement on the predictive value of 3D MRE in differentiating the histologic grade of HCC. Methods: 85 patients with pathologically confirmed HCCs were analyzed using 3D MRE imaging, two radiologists measured the tumor stiffness with three different ROI positioning methods. Intraclass correlation coefficient (ICC) was expressed in terms of inter- and intra-observer agreements. Kruskal–Wallis rank test or one-way ANOVA was used to compare the difference in MRE stiffness across the three-ROI positioning methods. Receiver operating characteristic curve analysis (ROC) was performed, and the area under curve (AUC) was measured to evaluate the diagnostic performance. Results: There were 64 (75%) well-or-moderately differentiated HCCs and 21(25%) poorly differentiated HCCs included finally. Almost excellent inter- and intra-observer agreements (all ICC > 0.82) were observed for all three-ROI methods, the volumetric method has the highest values (inter-observer ICC 0.967, intra-observer ICC 0.919, 0.926, respectively). The mean stiffnesses of poorly differentiated HCC obtained by two readers were significantly higher than well-or-moderately differentiated HCC with volumetric method (7.07 ± 1.57 Kpa, 5.00 ± 1.49 Kpa, and 6.85 ± 1.49 Kpa, 4.94 ± 1.48 Kpa, respectively) and three-ROI method (6.14 ± 1.71 Kpa, 4.91 ± 1.56 Kpa and 5.94 ± 1.61 Kpa, 4.84 ± 1.54 Kpa, respectively) but not on single-ROI method (p > 0.005), for the diagnostic performance, the highest area under the curve (AUC) with a value of 0.837, 0.812 by using the volumetric method, followed by the three-ROI method (0.713, 0.754) and single-ROI method. Conclusion: Different ROI positioning methods significantly affect HCC tumor stiffness measurements. The whole tumor volumetric analysis is superior to ROI-based methods for predicting the grade of HCC.